2014
DOI: 10.2174/1874840601407010006
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Silicon and Titanium Applications Influence Growth and Quality Characteristics of Annual Bedding Plants

Abstract: This study investigated the effects of foliar Si and Ti applications on annual bedding plant growth and quality in soilless media. The five annual plant species selected were geranium (Pelargonium x hortorum 'Elite Cherry'), impatiens (Impatiens walleriana 'Accent White'), pansy (Viola x wittrockiana 'Delta Premium Marina'), petunia (Petunia x hybrid 'Celebrity White') and snapdragon (Antirrhinum majus 'Montego Purple'). Sodium silicate (NaSiO 3) supplied foliar treatments of 0, 50, 100, 150 and 200 mg Si•L-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…At the same time, these authors noted a significant decrease in the flower diameter in other plant species as Lobelia erinus, Sutera grandiflora and the number of inflorescences of Argyranthemum frutescens as compared to plants that did not receive Si supplementation. The experiments by Whitted-Haag et al (2014) showed that the same biometric parameters in five tested plant species were positively affected by various Si doses (up to 200 mg·dm -3 ). However, the results of studies by Mattson and Leatherwood (2010) showed that certain species and cultivars of ornamentals did not respond to Si supplementation.…”
Section: Resultsmentioning
confidence: 88%
“…At the same time, these authors noted a significant decrease in the flower diameter in other plant species as Lobelia erinus, Sutera grandiflora and the number of inflorescences of Argyranthemum frutescens as compared to plants that did not receive Si supplementation. The experiments by Whitted-Haag et al (2014) showed that the same biometric parameters in five tested plant species were positively affected by various Si doses (up to 200 mg·dm -3 ). However, the results of studies by Mattson and Leatherwood (2010) showed that certain species and cultivars of ornamentals did not respond to Si supplementation.…”
Section: Resultsmentioning
confidence: 88%
“…The shortest plants were harvested from the control plots, whereas the highest from the plots treated with Ti at a dose of 6.8 g · ha -1 . Contrasting results were obtained by Jaberzadeh et al [19] and Whitted-Haag et al [16]. Jaberzadeh et al [19] reported that higher concentration of Ti (0.03%) in Triticum aestivum contributed to decreased plant height and improved biomass yield and seed parameters.…”
Section: Discussionmentioning
confidence: 87%
“…Jaberzadeh et al [19] reported that higher concentration of Ti (0.03%) in Triticum aestivum contributed to decreased plant height and improved biomass yield and seed parameters. According to Whitted-Haag et al [16] Ti supplementation (at 0, 25, 50, 75, and 100 mg · dm -3 ) in annual bedding plants (geranium, impatiens, pansy, petunia, and snapdragon) only slightly affected plant height but significantly changed stem diameter. In Impatiens walleriana stem diameter exhibited a linear decrease as Ti concentration increased (from 8.9 mm in control to 7.4 mm in the plants treated with Ti at 100 mg · dm -3 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Chlorophyll content in previous research has varied from plant-to-plant. (Whitted-Haag et al, 2014) found Ti applications to have linear increases and decreases in chlorophyll content, depending on the plant. The results were inconsistent.…”
Section: Chlorophyll Contentmentioning
confidence: 98%